Morphological alterations of the parotid gland of rats maintained on a liquid diet - Leal,Soraya Coelho (2003)
The purpose of this study was to analyze the morphological alterations that occurred in the parotid glands of rats maintained on a liquid diet compared to a solid diet. Thirty-six animals were randomly divided into two groups. The control group received a solid diet, and the experimental group received a liquid diet. The animals were killed after 8, 15 and 30 days. The glands were prepared for inclusion in paraffin and analyzed with a light microscope. The results showed a statistically significant reduction of the parotid gland weight of the animals from the experimental group compared to the control group at 15 and 30 days. The strongest morphological alteration displayed was the presence of cytoplasm vacuoles on the parotid glands of the animals maintained on the liquid diet. Specific stain techniques for glycoproteins and mucopolysaccarides could not identify the substances inside the vacuoles observed in the experimental animals. We conclude that a liquid diet caused atrophy of the parotid gland after 15 and 30 days.